Facilitating agency in Norwegian pupils struggling to stay in school—An alternative approach to emancipatory education - Tokheim, Ivan; Jobst, Solvejg; Dyngeland, Espen Søreide; Kråkenes, Maria Sundfør; Skrobanek, Jan (Frontiers in Education, 2024)
In this article we discuss a Norwegian alternative educational program which aids pupils struggling to stay in school. The practice displays an unconventional but promising approach to emancipatory education by facilitating agency in struggling pupils. We begin by providing some context on the Norwegian educational system and the Nordic model of education. Thereafter, we clarify our perception of educational equality and its underlying conditions. We then apply the chordal triad of agency as a heuristic framework for the qualitative analysis of our data material, consisting of three individual interviews, a focus group interview (N=6) and a guided tour at the location of the educational practice. The gathered testimonies suggest great potential in the program's ability at facilitating agency in at-risk pupils aged 9-16, thereby reducing chances of school dropout and social exclusion. Based on respondents' reflections, we conclude with some discussion comparing the studied practice to the formal Norwegian education system and its shortcomings in accommodating for certain pupil groups struggling to adapt to traditional schooling.